Pengaruh Autogenic Training Terhadap Nyeri Pada Pasien Post Percutaneous Coronary Interventions (PCI) di Rumah Sakit Umum Daerah Kota Bogor - Atlantic, Mia; Jumaiyah, Wati; Purnamawati, Dewi; Sofiani, Yani; Susanto, Budi; Yunus, Muhammad Iqbal (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
Percutaneous Coronary Interventions (PCI) is a medical procedure used to address coronary artery disease. Despite effectively improving heart blood flow, patients often experience pain and discomfort after PCI. This study evaluates the impact of autogenic training on reducing patient pain after PCI. In a quasi-experimental design with a control group, 72 patients who had recently undergone PCI were involved. The intervention group received structured autogenic training, while the control group received no intervention. Pain was measured using a numeric rating scale. Multiple linear regression analysis results showed p-values for the group at 0.009, spiritual variable at 0.284, and self-efficacy variable at 0.494. However, excluding the self-efficacy variable led to an Odds Ratio change of over 10% for other variables. Thus, the self-efficacy variable was re-introduced in the second stage, yielding p-values of 0.003 for the group and 0.458 for self-efficacy, after excluding the spiritual variable due to OR value change below 10%. In the final model, group p-value was 0.008, spiritual was 0.284, and self-efficacy was 0.494. Autogenic Training strengthens post-PCI pain management, providing a safe additional option for patients. The approach aids PCI recovery, reinforcing pain management strategies. By offering relaxation therapy like Autogenic Training, patients receive a safe and beneficial supplementary avenue for managing post-PCI pain